PENDIDIKAN KARAKTER DI SEKOLAH DASAR PADA ERA PERKEMBANGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Umayah, Rida (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2019)
The application of character education is a new challenge for elementary school teachers in the development of information technology applying character education. Observations made on students at SDN Rembang 2 Blitar City resulted in the development of opinions and observations from discussions conducted with teachers on the emergence of unfavorable dependencies and changes in the system of moral order and values ​​of students during the use of information and communication technology. The application of character education is carried out in collaboration with parents, the community and the government with rules. Control and binding rules can be done to familiarize students in using information technology properly. Supervision of primary school students in using devices becomes part of the responsibilities of parents, teachers, the community.